PENGGUNAAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SEJARAH KELAS VIII SMP NEGERI 3 TAMBANG - ', Esapniar; ', Isjoni; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The Snowball Throwing learning model is an instructional model that divides the students into groups, which each group member makes a question on a piece of paper and shapes it like a ball, then the ball is thrownto another student for a specified duration of time, which then each student answering questions rom te ball e obtained. By applying this learning model can train students to be more responsive to receive messages from others and convey the message in a group and can solve a problem given to him, but also to improe student activeness in the learning process, creating studens wo are more critical and analysis in learning because by using tid model students as much as possible more understanding of learning materials. Te purpose of this research is: 1) To know the implementation of teacing activities of teachers by using the model of Snowball Throwing on students of grade VIII.1 SMP N 3 Tambang, 2) To know the implementation of learning activities of students by using the model of Snowball Throwing on students of grade VIII.1 junior N 3 Mine, 3) To know the extent of the success of teaching and learning using the Snowball Throwing model on the students of grade VIII1 SMP N 3 Tambang. This study was conductedin 2 cycles. Subjectsin this study were all students class VIII1 SMP N 3 Tambang amounting to 33 people. Technical analysis of data in this study using descriptive quantitative. The results showed that the activity o teachers during two cycles increased in the first cycle of meeting I obtained a score of 18 with good category, increased in the second meeting to 20 with very good category, and increased again in cycle II meeting I obtained score 25 with very good category, and increase at meeting II with get score 26 with good category. Student activity increased in cycle I meeting I got score 666 with enough category, increased at second meeting to 685 with good category, icrease in cycle two meeting I got score 700 with good category, and increased at the second meeting with a score of .726 with good category, and student learning outcomes increased with the average daily recurrence of cycle I was 68.63% and increased in daily repetition of cycle II with an average score of 72,87%, it can be concluded that by using Snowball Throwing model can increase teacher activity, student activity and test result of learning subject of student history class VIII.1 SMP N 3 Tambang.Keywords: Snowball Throwing Learning Model, Learning Outcomes